On the mechanism of zirconium nitride formation by zirconium, zirconia and yttria burning in air; Journal of Solid State Chemistry; Vol. 230 - Malikova E. A. Ekaterina Aleksandrovna; Pautova Yu. I. Yuliya Igorevna; Gromov A. A. Aleksandr Aleksandrovich; Monogarov K. A. Konstantin Aleksandrovich; Larionov K. B. Kirill Borisovich; Teipel U. Ulrich (2015, 2015)
Title screen